Natural resource based traditional Folk art of Purba Medinipur, On the way to extinction day by day - Dash, Anima (IJRDO - Journal of Social Science and Humanities Research, 2018)
Every region of the world have its own culture and its expressed by various type of art forms. Folk Art one of the unique artform which expressed the regional traditional culture. It rooted in tradition of our society that come form community and culture. This art also expressed our cultural values and aesthetic. Like other region of the world there are certain folk artfroms of Purba Medinipur district such as pats (Scroll painting , Bamboo art, Dokra art, shoal art etc,). After independence, the government took various step to protect these artform. Currently there is a concern, use of advancetechnology and globalization as well as our negligence towards culture narrowed down our district heritage folk art.